2015
DOI: 10.1007/s11295-015-0889-3
|View full text |Cite
|
Sign up to set email alerts
|

Provenance variation and within-provenance genetic parameters in Eucalyptus urophylla across 125 test sites in Brazil, Colombia, Mexico, South Africa and Venezuela

Abstract: Provenance and within-provenance genetic variation for stem volume growth in Eucalyptus urophylla was examined in a large trial series of 125 provenance/ progeny tests in five countries. In general, heritability (within-provenance) for age-3 volume was around 0.15 for Brazil, Colombia, Mexico, and South Africa and was slightly lower in Venezuela, where tree volume was lower. Provenances from all seven islands in Indonesia where the species occurs were included in the trials. Substantial provenance variation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 15 publications
5
19
0
3
Order By: Relevance
“…Our results coincide with the relatively high type B correlations (above 0.55) reported by Wei and Borralho (1998), and Hodge and Dvorak (2015) for E. urophylla. Nirsatmanto et al (1996) reported moderate (0.49 for DBH) type B correlations between two sites in Indonesia, but indicated that predicted gains of the selection index across the sites were still greater than those of the indices at each site.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results coincide with the relatively high type B correlations (above 0.55) reported by Wei and Borralho (1998), and Hodge and Dvorak (2015) for E. urophylla. Nirsatmanto et al (1996) reported moderate (0.49 for DBH) type B correlations between two sites in Indonesia, but indicated that predicted gains of the selection index across the sites were still greater than those of the indices at each site.…”
Section: Discussionsupporting
confidence: 93%
“…Various levels of GxE have been reported for E. urophylla (Mori et al 1990, Wei and Borralho 1998, Hodge and Dvorak 2015. Mori et al (1990) for example, have reported losses in volume of 26.7% due to GxE.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Entre as características favoráveis, destacam--se: alta taxa de crescimento, adaptação a diversas condições edafoclimáticas, boa capacidade de rebrota, resistência ao déficit hídrico e ao fungo causador da ferrugem (Puccinia psidii), a murcha do eucalipto (Ceratocystis fimbriata) e aos cancros do eucalipto (Chrysoporthe cubensis e Coniothyrium zuluense) (CARVALHO et al, 1998;FIRMINO et al, 2013;PALUDZYSZYN FILHO;PINTO et al, 2014); além de tolerância a vespa da galha (Leptocybe invasa) (THU et al, 2009). Em função disso, tem sido frequentemente utilizada para compor o híbrido com E. grandis, resultando em plantações clonais com melhor tolerância a doenças e maior densidade básica da madeira (HODGE;DVORAK, 2015). Em termos de empregabilidade, o E. urophylla pode ser utilizado na produção de celulose e papel, lenha e carvão vegetal, além da fabricação de postes, aglomerados e compensados (SELN;MITLÖHNER, 2011).…”
Section: Introductionunclassified